Names, pseudonyms and anonymity in online interactions: a study of name policy on news24, the daily Maverick, and 4chan. - Donald, Katherine Faye (My University, 2017)
This research investigates real names, pseudonyms, and anonymity online. From its small beginning as a research tool, the internet has grown radically and been increasingly incorporated into people’s daily lives. Simultaneously, as the internet has grown and changed, so have its uses, and perceptions of the naming practices used on it. Attitudes towards acceptable name use online have changed over time. Social networking sites have had a strong influence on name usage policies. This research examines how these attitudes have changed, and the implications of real names, pseudonyms and anonymity for behaviour on the internet and privacy. The radically disembodied nature of online communication lends itself to disinhibition, which in turn has resulted in online communications’ reputation for trolls and abusers. Contrary to the common assumption that the use of real names offline indicates the legitimacy of using real names online, online and offline communications are radically different. Online communications have very different considerations regarding privacy, identity theft, the digital footprint, and collapsed context, many of which are not present in offline communications. This paper examines naming policies and site structure through two case studies. The first case focuses on News24 and the Daily Maverick, both of which are South African news sites. Due to the need for rational and polite discourse, these implemented real name policies in order to enforce good behaviour amongst their users. In both cases, the real name policies failed. The second case study is that of 4chan, the American image board site. 4chan does not require any login process, and its users are typically anonymous. Despite being notorious for trolls, illegal content, and its image board /b/, the site’s architecture, along with the way that posts are created and then kept alive, mean that the site can be effective at moderating the kinds of content that it deems appropriate for each of its boards. Despite the contrasting nature and purposes of the news sites and 4chan, there are lessons to be learnt from the failure of real name policies, and the architecture and set up of sites which can be used to enforce particular behaviours. Furthermore, despite the ephemeral and shifting nature of 4chan, identity and a sense of belonging remain important to its users, hinting at the importance of a sense of identity to site members and the role of this identity in ensuring that users adhere to the norms.
A research report submitted to the Faculty of Arts, University of the Witwatersrand, Johannesburg, in partial fulfilment of the requirements for the degree of Master of Arts, Johannesburg, 2017
Keywords: Privacy, Right of--South Africa; Internet--Law and legislation--South Africa; Data protection--Law and legislation--South Africa; Identity (Psychology)--South Africa